The brightening glance : imagination and childhood / Ellen Handler Spitz. - Spitz, Ellen Handler. (Anchor Books, 2007)
A study of the aesthetic development of children follows the evolution of the imagination between the ages of two and twelve, explaining how the sensory, perceptual, and imaginative lives of youngsters intersects with emotional development.